Bone graft versus non-bone graft for treatment of calcaneal fractures: A protocol for meta-analysis. Issue 2 (15th January 2021) - Tian, Heng; Guo, Wenlai; Zhou, Jinlan; Wang, Xiaoyue; Zhu, Zhe
Abstract: Background: Calcaneal fractures are a prevalent form of injury caused by high-energy trauma. This study aimed at investigating whether bone graft and non-bone graft are essential for the internal fixation of calcaneal fractures. A meta-analysis of relevant clinical studies evaluated radiographic parameters, functional outcomes, and complications that offer practical recommendations on the suitability of bone grafts for the management of Calcaneal fractures. Methods and analysis: This study performed a comprehensive search on PubMed, EMBASE, and Cochrane electronic to retrieve related clinical studies. The studies incorporated in our meta-analysis were identified after doing a preliminarily screening, reading of the full-text articles, and eliminating repeated studies. After quality assessment and data extraction, the standardized mean difference and risk ratio were selected as effect sizes. The data on Böhler angle, Gissane angle, calcaneal height, American Orthopaedic Foot and Ankle Society hindfoot scores, Maryland Foot Evaluation, and rate of wound infection were analyzed using Revman 5.3 software (Cochrane Collaboration). Results and Conclusions: This study did not reveal any significant differences ( P  < .05) in both Böhler and Gissane angles, calcaneal height, American Orthopaedic Foot and Ankle Society hindfoot scores, Maryland foot evaluation, and rate of wound infection between the 2 groups. Due to the lack of a large sample of comparative studies, the use of bone grafting for the management of calcaneal fractures requires additional substantiation.